Far-infrared opacity sources in Titan's troposphere reconsidered - de Kok, R; Irwin, P; Teanby, N (2010)
We use Cassini far-infrared limb and nadir spectra, together with recent Huygens results, to shed new light on the controversial far-infrared opacity sources in Titan's troposphere. Although a global cloud of large CH4 ice particles around an altitude of 30km, together with an increase in tropospheric haze opacity with respect to the stratosphere, can fit nadir and limb spectra well, this cloud does not seem consistent with shortwave measurements of Titan. Instead, the N2-CH4 collision-induced absorption coefficients are probably underestimated by at least 50% for low temperatures. © 2010 Elsevier Inc.